Semantics of Arabic Verbal Stems Derived From Triliteral Roots - Muftić, Teufik (Prilozi za orijentalnu filologiju, 2017)
The Arabic (classical) language lexically (as well as morphologically) is the richest among all the Semitic languages. The extraordinary wealth of roots, the number of which amount to 10.000, testifies to that. The most numerous and most important among them are definitely the roots with three root-consonants, or radicals (of which there can be from 1-5 in Arabic). There are 6723 such roots, i. e. triliterals (according to our data on the basis of the corpus of „Lisānu-l-'Arab“ dictionary by Ibn Manẓür). The second, by their number and importance, are the roots with four radicals, i. e. quadrilaterals, of which there are 2516 in the mentioned dictionary. In Arabic the verbs can be derived from these two kinds of roots only. Further morphological derivation is far more developed in trilaterals, and it will be dealt with in this paper only partially, while the present work mostly deals with the semantics of the (verbal) forms derived from trilaterals, and up to a point, their nominal derivatives. The first part of the paper (I. Introductory review of the basic group, p. 37) deal briefly with the first and the basic form of Arabic verbs derived from trilateral roots. In that group, on the basis of different vocalization, various verbs can already be formed from the same root, which beside that morphological difference, can also differ semantically. By that inner flexion, i. e. alternation of the vocalism itself in the first group, the passive forms which also bring in certain changes in the shades of the basic meaning of some of the triliterals are formed. Also the reaction of a verb affects considerably the meaning, both in the first, as well as in the derived classes; the fact, whether it is used as a transitive or an intransitive verb without a preposition, or with one or more prepositions, which more or less can change his basic, original meaning sometimes even make it to mean something quite opposite. Besides, one should keep in mind that very often a certain verb can be polysemous, i. e. can have two or more basic meanings. That could, among other things, be the result of the specific semantic development of that verb, or possibly, by convergence of the two originally morphologically different roots, so that, because of their being phonetically identical, does not mean that they are also semantically identical, but that their previously different meanings have remained intact as a part of the living usage.